Identification of RNF114 as ADPr-Ub reader through non-hydrolysable ubiquitinated ADP-ribose - Max S. Kloet; Chatrin Chatrin; Rishov Mukhopadhyay; Bianca D. M. van Tol; Rebecca Smith; Sarah A. Rotman; Rayman T. N. Tjokrodirijo; Kang Zhu; Andrii Gorelik; Lucy Maginn; Paul R. Elliott; Peter A. van Veelen; et al. (Nature Communications)
Abstract Crosstalk between the post-translational modification processes of ubiquitination and ADP-ribosylation occurs in DNA-damage- and immune-responses, in addition the physical linkage of ADP-ribose and ubiquitin is found during bacterial infection. Here, we study the ubiquitination of ADP-ribose mediated by human Deltex E3 ligases and the subsequent fate of the formed hybrid post-translational modification. We prepare a non-hydrolysable ADPr-Ub probe that we employ in a proteomics approach and identify RNF114 as an interacting protein. Using biophysical and biochemical experiments, we validate that RNF114 preferentially interacts with ubiquitinated ADP-ribose over non-modified ubiquitin. Subsequently, RNF114 can elongate the ubiquitinated ADP-ribose with a K11-linked ubiquitin chain. Using domain deletion analysis, we pinpoint the tandem zinc fingers and ubiquitin interacting motif (ZnF2 + ZnF3+UIM) domains of RNF114 to be crucial for recognising ubiquitinated ADP-ribose. Moreover, these domains are essential for the recruitment of RNF114 to the sites of laser-induced DNA damage.